COMPARATIVE ANALYSIS OF THE EFFICACY OF BIOCOMPATIBLE AND HIGH-EFFICIENCY HYDROXYAPATITE-BASED PASTES IN TREATMENT OF DENTIN HYPERENSITIVITY - Rajabova Mohira Ergashovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Dentin hypersensitivity (DH) is a common and painful clinical condition characterized by short, sharp pain arising from exposed dentin in response to various stimuli. The search for effective, biocompatible, and long-lasting desensitizing agents remains a key focus in modern dentistry. Hydroxyapatite (HAp)-based pastes have emerged as a promising treatment due to their biomimetic properties, which allow them to occlude dentinal tubules and integrate seamlessly with the natural tooth structure.